2018
DOI: 10.1152/ajpheart.00558.2017
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of phase singularities on the spiral wave tail: reconsideration of capturing the excitable gap

Abstract: The action mechanism of stimulation toward spiral waves (SWs) owing to the complex excitation patterns that occur just after point stimulation has not yet been experimentally clarified. This study sought to test our hypothesis that the effect of capturing excitable gap of SWs by stimulation can also be explained as the interaction of original phase singularity (PS) and PSs induced by the stimulation on the wave tail (WT) of the original SW. Phase variance analysis was used to quantitatively analyze the postsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To discuss SW dynamics after conduction blockage, occurrence and annihilation dynamics of SWs should be considered. In a previous study about point stimulation during SW excitation, SW dynamics after conduction block were also discussed [35]. The study reported that conduction block generates two SWs, one clockwise and another counterclockwise.…”
Section: Mechanism Of Sw Drift Along the Cooling Regionmentioning
confidence: 99%
“…To discuss SW dynamics after conduction blockage, occurrence and annihilation dynamics of SWs should be considered. In a previous study about point stimulation during SW excitation, SW dynamics after conduction block were also discussed [35]. The study reported that conduction block generates two SWs, one clockwise and another counterclockwise.…”
Section: Mechanism Of Sw Drift Along the Cooling Regionmentioning
confidence: 99%
“…As shown in Figure 1, since its first use for optical mapping in 2007, blebbistatin has all but replaced the other available EC uncouplers. In fact, in the last three years alone, blebbistatin was used twice as often (1,29,36,41,51,56,59,69,74,76,78,83,85,87) as any other uncoupler for imaging applications (25,27,33,46,54,55,80). The use of BDM/DAM and CytoD for optical mapping has essentially ceased, yet due to its lower cost, BDM/DAM may still be a reasonable choice for larger animal (i.e., non-rodent) studies (10,23,25,35,52,70,77), which require larger amounts of an EC uncoupler (72).…”
Section: Excitation-contraction Uncouplingmentioning
confidence: 99%
“…The details of the algorithm are described in other studies. [24][25][26] The phase value of each pixel in the camera image was calculated by applying reverse normalization and Hilbert transform to the OPT signal. using both mapping methods, and the activation pattern estimated by EXT was compared with that estimated by OPT.…”
Section: Derivation Of Phase Mapsmentioning
confidence: 99%